Simulation of water dynamics in two irrigated soils - Barão,L. (2010)
Simulation results for water content distribution obtained with HYDRUS, RZWQM and MOHIDLAND models were compared with field data. These models differ mainly in calculating root water uptake and computing crop water requirements. Simulations were carried out in different horizons of an Hortic Anthrosol and an Eutric Fluviosol, located in the Alentejo region (Portugal). Soil water content was measured, with a TDR system at different depths. Soil hydraulic properties were determined in the laboratory, and described in HYDRUS and MOHIDLAND with the Mualem-van Genuchten, and in RZWQM with the modified Brooks and Corey equations. Reference evapotranspiration was calculated with the Penman-Monteith and the Shuttleworth-Wallace method using atmospheric data from the meteorological stations located near the field plots. Partition between transpiration and evaporation was calculated using the Leaf Area Index values, and the RZWQM crop module. Results show a good agreement between model simulations and field measurements for the three models.